Communication Management of the Religious Harmony Forum of DKI Jakarta in Overcoming Intolerance and Radicalism - Dudi Iskandar; Indah Suryawati; Liliyana Liliyana (Communicatus: Jurnal Ilmu komunikasi, 2022)
In two national surveys on tolerance, equality, and cooperation among religious communities conducted by the Ministry of Religious Affairs at 2019 and 2021, the DKI Jakarta harmony index was below the national average. This study aims to capture the activities and communication management patterns of the Religious Harmony Forum of DKI Jakarta, especially in overcoming intolerance and radicalism. Both intolerance and radicalism are often cited as triggers for the emergence of religious disharmony in DKI Jakarta. The results of this study show that, first, the communication management of the DKI Jakarta FKUB is not well-organized as a modern organization that always follows the developments based on communication and information technology. Second, the problem of the forum lies in the weakness of social regulations and government actions in implementing recommendations. Third, the role of this forum must be wider, and more innovative to support the country at a macro level to prevent intolerance and radicalism.